2004
DOI: 10.1080/00102200490487175
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen–oxygen Induction Times Above Crossover Temperatures

Abstract: Ignition in hydrogen-oxygen systems above crossover temperatures and under various conditions of pressure and composition is addressed computationally and by asymptotic methods. Different descriptions of the detailed chemistry are evaluated through comparison of computed and measured ignition times, and a balance between accuracy and simplicity is struck in selecting rate parameters to be used in investigating reduced chemistry. Through numerical calculations for isobaric, homogeneous, and adiabatic hydrogen-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…Previous theoretical analyses have shown that high-temperature ignition histories can be computed accurately from integrations of unsteady homogeneous equations in isobaric adiabatic systems, which yield analytic expres-sions for the induction time above crossover when the effects of reactant consumption and heat release are both neglected during the induction period [1]- [7]. Ignition events described by the overall reaction 3H 2 +O 2 → 2H 2 O+2H have ignition times t i that increase linearly proportional to (2k 1 …”
Section: Reduced-chemistry Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous theoretical analyses have shown that high-temperature ignition histories can be computed accurately from integrations of unsteady homogeneous equations in isobaric adiabatic systems, which yield analytic expres-sions for the induction time above crossover when the effects of reactant consumption and heat release are both neglected during the induction period [1]- [7]. Ignition events described by the overall reaction 3H 2 +O 2 → 2H 2 O+2H have ignition times t i that increase linearly proportional to (2k 1 …”
Section: Reduced-chemistry Descriptionmentioning
confidence: 99%
“…At sufficiently high temperature, ignition is characterized by a long in- 2H 2 O+2H describes accurately the growth of H radicals, the rate of H-atom production being given by twice that of reaction 1 minus that of reaction 4 [7].…”
Section: Reduced-chemistry Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in [2,3], hydrogen ignition below crossover takes place as a thermal explosion, controlled by slow reactions involving hydroperoxyl and hydrogen peroxide, whereas the radicals H, O, and OH, which dominate the branched-chain explosion that characterizes ignition above crossover [4], are consumed at a fast rate, with the result that these species follow closely a steadystate approximation. The most important elementary reactions are 2HO 2 M !…”
Section: Introductionmentioning
confidence: 99%
“…5, one can expect the steady-state approximation for all four intermediates to provide a very accurate description for φ = 0.3 and less accurate results for φ = 0.5. This situation is different from that encountered in autoignition, in which HO 2 is not in steady state, OH and O obey good steady states only under fuel-rich conditions, and the H steady state is accurate only for φ 0.05 [18].…”
Section: One-step Reduced Kineticsmentioning
confidence: 77%